(untitled) (Journal of University of Babylon for Engineering Sciences, 2023)
The evaluation was based on the plant operation data such as BOD5, COD, TSS, T.N, PO4, NH3, SO4, NO3, Cl, and Oil&Grease for the period of 11months from Oct. (2020) to Aug. (2021). Data taken from a laboratory in the wastewater treatment plant and compiled in Excel software. The results showed that the efficiency of removal of BoD5, COD, TSS, T.N, PO4, NH3, SO4, NO3, CL, and O&G was 92.68%,78.97%,94.27%,62.61%,81.83%,83.32%, 8.71%,61.53%,12.29%, and 88.88% respectively on a monthly basis. Accordinig, it can be recommended that the Al-Muamirah wastewater treatment plant has an acceptable efficiency except for the efficiency of sulfates and chlorides that are not acceptable please treat them in the future. A multivariate statistical technique of the data has been attempted by applying cluster analysis using a statistical (SPSS). Cluster analysis shows that months (December20, February21, October20, January21 and November20) indicate a good level of treatment compared to that of (March21, May21, August21, Jun21, July21 and April21).